Диверсифікація виробництва як фактор підвищення економічної ефективності землекористування - Печко, Володимир Сергійович (My University, 2016)
У статті розглядаються проблеми мінімізації рівня ризику при оцінки ефективності землекористування. Робиться теоретичний огляд проблеми, зокрема понять «диверсифікація виробництва» та «ризик». Ціллю даної роботи є оцінка впливу диверсифікації на економічну ефективність з врахуванням ризику ціни та урожайності культур. Наведений авторський методичний підхід який дозволяє врахувати вплив рівня варіативності ціни та урожайності на економічну ефективність використання земель. На підставі даних сільськогосподарських підприємств Харківської області, було розраховано рівень відносної доходності сівозміни з врахування з врахуванням ризиків. Аналіз взаємозв'язку коефіцієнта спеціалізації та рівня відносної доходності сівозміни дав можливість встановити, що величина рівня відносної доходності буде максимальною при значення коефіцієнта спеціалізації 0,37. The subject matter of this article consists in an analysis of the factors determining the risk level as well as the risk level related to the activities of agricultural enterprises. A study of the "risk" concept has been undertaken. It has been noted that one of the ways to avoid risk is to diversify production. This research is aimed at assessing the risk factors in the activities of agricultural enterprises. The risk factors that have been studied included the price and the yield across a group of cereal and industrial crops. It is stated that fluctuation of prices can clearly be seen across all crops. They are generally associated with their fall in August through October and rise in January through May. In 2013-for corn, sunflower seed and rye, and in 2014-for com, sunflower seed and rapeseed respectively. A correlation analysis along with calculation was performed to identify the interdependence of changes in prices for certain crops. The correlation analysis of the dynamics of yield allowed to find out that the yield of wheat crops is most strongly associated with the yield of corn and rye crops, and least strongly - with the yield of sunflower crops. As for sunflower crops, the closest relationship was found to be present with the yield of rape crops, and it was least strongly associated with the yield of wheat and barley crops. These results make it possible to predict the probability of simultaneous 'failure" for two or more crops. Research findings emphasize that the main focus of minimizing these risks should be the diversification of production which should be associated with the increase of sales and forward integration. Besides, one should develop such pattern of receipts and expenditures in the production of agricultural products that would ensure the maximum effect with minimum possible risks.
Keywords: ризик; диверсифікація; ефективність виробництва; стійкість; спеціалізація; risk; diversification; correlation dependence; price; yield